ANALYSIS OF THE REASONING LOGIC VIOLATION IN DECISION MAKING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
This study deals with reasoning logic in decision making. Three major classes of decision making theories are outlined Possible situations in which preference misrepresentation might take place are analyzed. The reasons for the violation of reasoning logic œe examined andpossibilities of overcoming it are considered.